PERILAKU PENGUNJUNG DALAM MEMILIH LOKASI PARKIR PADA KAWASAN WISATA MALIOBORO DI YOGYAKARTA - Prasetyan, Putri; Manullang, Okto Risdianto (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
Malioboro Street is one of street in Yogyakarta City that become tourist destination, especially for shopping, for local and foreign tourists that is visited by more than 4000 people every day so that the need for parking in this area was high. The Yogyakarta City Government responded by providing Abu Bakar Ali Parking Building at north of Malioboro Street and imposing a parking restriction throughout the area to maintain its parking neatness. However, the visitors still prefer to park their vehicles in the parking bags around Malioboro Street. The purpose of this study is to determine the behavior of visitors in choosing parking location at Malioboro Tourism Area during weekdays and weekend using Importance Performance Analysis (IPA) method. It is known from the analysis result that Abu Bakar Parking Building performance is still not accommodate visitors’ need because of its location that does not suit their travel purpose and destination. The performance of this building is said to be not good because based on the analysisit is found that the behavior of Malioboro Touism Area visitor is influenced by travel purpose and parking service characteristics. In addition, visit time, ie weekdays and weekend also influences the visitor’s behavior in choosing parking location. For that reason, in determining the location of parking buildings in the tourism area, the city government should think about visitor’s behavior and their visit time to in order to optimalize the usage of the parking building provided.